ADULT WOMAN WITH INTRA-ORAL EPIDERMOID CYST - Chaudhry, Sadia; Hannan, Abdul; Ikram, Umar (Journal of Ayub Medical College Abbottabad, 2013)
Epidermoid cyst is a rare, slow growing lesion of head and neck region. Its rarest site of presentation is intra-oral. It presents later in life, while taking its time to grow to a significant size, causing other complaints as dyspnoea and dysphagia. We present here a case report of epidermoid cyst at a very rare and unexpected site of presentation. Patient presented in ENT OPD with complaints of large intra-oral midline swelling and associated complaints of dyspnoea and dysphagia. Patient was admitted and operated upon with intra-oral approach, producing good results. It should be kept in mind as one of the differential diagnoses when dealing with long standing intra-oral swellings. Keywords: Epidermoid Cyst, Mouth Floor, Congenital, Histology